Щодо міжгалузевих зв'язків права у сфері інтелектуальної власності - Гаєвая, Олександра Валентинівна (НТУ "ХПІ", 2016)
У статті зіставляються міжгалузеві зв’язки права інтелектуальної власності з іншими інститутами приватного та публічного права. Визначаються функції права інтелектуальної власності. Розкривається сутність права інтелектуальної власності та її місце в системі права, зобов’язання в галузі інтелектуальної діяльності, загальні норми зобов’язального права: про сторони і види зобов’язань, виконання та способи забезпечення виконання, відповідальність за їх порушення і припинення зобов’язань. Особлива увага приділяється міжгалузевим зв’язкам права інтелектуальної власності.

In the article the interbranch ties of intellectual property rights with other institutions of private and public law have be en compared. The functions of intellectual property rights have been determined. Intellectual property is inseparably connected with the results o f people intellective creative activity. The article the essence of intellectual property rights and its place in the system of law has been disclosed. A particular attention is given to the interbranch ties. For persons whose result of their activity is protected one, intellectual property is an exclusive right, privilege giving them the opportunity to get a full set of property and non- property goods with the help of their activity product. For entrepreneurs, intellectual property is part of their property being used by them during their business activity with the purpose of making profit. For the consumers, int ellectual property is certain non-property goods (product of other one labor) being used by them to meet their own needs such as aesthetic enjoyment, spiritual development, etc. The essence of intellectual property means enshrined by law rights being the result of the intellectual activity in industrial, scientific, literary and artistic spheres. So, the concept of intellectual property was enshrined at the international legal practice on the legislative level and as the result of this appeared also in the national legislation of Ukraine.
Regarding of the interbranch ties of law in the field of intellectual property
Keywords: право цивільне; право патентне; знак товарний; зразок промисловий; винахід; civil law; patent law; trademark; invention